Cell numbers and in vitro responses of leucocytes and lymphocyte subpopulations following maximal exercise and interval training sessions of different intensities - Fry, R W; Morton, A R; Crawford, G P; Keast, D (European journal of applied physiology and occupational physiology, 1992)
In vitro lymphocyte function and the mobilisation of peripheral blood leucocytes was examined in eight trained subjects who undertook an incremental exercise test to exhaustion and a series of interval training sessions. Venous blood samples were obtained before the incremental test, immediately after, and 30, 60, and 120 min after the test. Interval training sessions were undertaken on separate days and the exercise intensities for each of the different sessions were 30%, 60%, 90% and 120% of their maximal work capacity respectively, as determined from the incremental exercise test. There were 15 exercise periods of 1-min duration separated by recovery intervals of 2 min in each session. Venous blood samples were obtained immediately after each training session. Significant increases in lymphocyte subpopulations (CD3+, CD4+, CD8+, CD20+, and CD56+) occurred following both maximal and supramaximal exercise. This was accompanied by a significant decrease in the response of cultures of peripheral blood lymphocytes to Concanavalin A (ConA), a T-cell mitogen. The state of lymphocyte activation in vivo as measured by CD25+ surface antigen was not, however, affected by acute exercise. The total number of lymphocytes, distribution of lymphocyte subpopulations and in vitro lymphocyte response to ConA had returned to pre-exercise levels within half an hour of termination of exercise but serum cortisol concentrations had not begun to fall at this time. There was a significant decrease in the CD4+:CD8+ cell ratio following exercise; this was more the result of increases in CD3-CD8+ cells (CD8+ natural killer cells) than to CD3+CD8+ cells (CD8+ T-lymphocytes). Decreased responsiveness of T-cells to T-cell mitogens, postexercise, may have been the result of decreases in the percentage of T-cells in postexercise mixed lymphocyte cultures rather than depressed cell function. The cause of this was an increase in the percentage of natural killer cells which did not respond to the T-cell mitogen. The results indicated that while a substantial immediate in vitro "immunomodulation" occurred with acute exercise, this did not reflect an immunosuppression but was rather the result of changes in the proportions of reactive cells in mononuclear cell cultures. We have also demonstrated that the degree of the change in distribution of lymphocyte subpopulation numbers and responsiveness of peripheral blood mononuclear cells in in vitro mitogen reactions increased with increasing exercise intensity. Plasma volume changes may have contributed to some of the changes seen in leucocyte population and subpopulation numbers during and following exercise.